Chemistry and origin of the Mayo Kila sapphires, NW region Cameroon (Central Africa): Their possible relationship with the Cameroon volcanic line. (June 2016) - Paul Mbih, Kemeng; Meffre, Sebastien; Yongue, Rose Fouateu; Kanouo, Nguo Sylvestre; Jay, Thomson
Abstract: Mineralogical, chemical and geochronological studies constrained the origin of sapphires from Mayo Kila, Northwest Cameroon. The sapphires are mostly blue, with sizes ranging from 2 to 5 mm. The pale blue grains are transparent, whereas, other corundums are transparent to translucent and/or opaque. The sapphires are dominantly euhedral to sub-hedral with few polished lustrous grains, acquired features during moderate to short distance transport from a proximal source rock. Solid inclusions are limited to rutile and zircon. Trace element analysis of sapphires shows significant concentration (in ppm) in some elements: Fe (2208–14, 473), Ti (82–1783), Ga (77–512), Mg (0.9–264.9), Cr (b.d.l −168) and V (1.3–82). The other elements (e.g. Sn, Nb, Ta, Th, Zr, Ni, Ce) are generally below 10 ppm. The calculated ratios for some of the selected elements show an extreme variation: Fe/Mg (43–3043), Fe/Ti (2–76), Ti/Mg (1–328), and Ga/Mg (0.4–363). They are dominantly corundum crystallized in alkaline magma (s) with few from metamorphic source (s). Trace elemental features with Hf (13, 354–26, 238 ppm), Th (4018–45, 584 ppm) and U (7825–17, 175 ppm), and Th/U (0.39–2.65) found in zircon inclusions are compatible with quantified values in magmatic crystallized zircons. The Cenozoic age (mean of 30.78 ± 0.28 Ma) obtained for zircon inclusions is close to the age of some igneous rocks found within the Cameroon Volcanic Line (e.g. rocks of the Mount Oku: 31–22 Ma), showing the same period of formation. The most probable source of the zircon host sapphires is the Oku Mountain located SW of Mayo Kila. Highlights: Sapphires from NW Cameroon are characterized to understand their genetic history. The sapphires were grown within alkaline magmatic and metamorphic environments. Zircon inclusions in part of the sapphires are Hf-U-Th enriched. Those inclusions were crystallized during Lower Cenozoic. Their source areas are probably within the CVL.